A method for preparing film-blown particles, its products and applications
Through the step-by-step addition method of high-substitution esterified starch and high-content talc powder, the problems of low talc powder addition and insufficient starch substitution in the prior art are solved, the mechanical properties and degradability of plastic products are improved, and the More even material mixing and improved waterproofing.
Patent Information
- Application Number
- CN202310338343.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-31
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2043-03-31
AI Technical Summary
The amount of talc powder added in the existing process is low, which cannot effectively improve the mechanical properties of plastic products. Moreover, high-content talc powder is easy to delaminate when mixed with other materials, and the degree of starch substitution is low, resulting in poor modification effect.
The preparation method of high-substituted esterified starch and high-content talc powder is adopted to improve the gel texture and hydrophilicity of starch through esterification treatment. The talc powder and PBAT are added in steps to ensure uniform mixing of materials, using vinyl acetate and Acetic anhydride is used as an esterifying agent and is subjected to vacuum negative pressure esterification.
It improves the mechanical properties and degradability of plastic products, solves the problem of mixed layering of high-content talc powder, enhances the tensile strength and elongation of breaking of the material, and improves waterproofing performance.
Smart Images

Figure BDA0004157256290000111
Abstract
Description
Technical Field
[0001] The invention relates to the field of plastic raw materials, and in particular to a method for preparing film-blowing particles and a product and application thereof. Background Art
[0002] With the rapid development of plastic industry technology, more and more plastic products have entered people's lives. However, the poor mechanical properties of plastic products and their difficulty in degradation have also brought a lot of troubles to people. The good availability and biodegradability of starch make it a good raw material for degradable materials, while the addition of talcum powder can effectively increase the forming shortening speed of plastics and play a role as a skeleton, reducing manufacturing costs while improving mechanical properties and stability.
[0003] CN108059804A provides a PBAT degradation masterbatch and a preparation method thereof, wherein the PBAT degradation masterbatch is made of the following components in mass percentage: 10%-20% pigment, 4%-7% glycerol, 10%-15% starch, 2%-4% monoglyceride, 2%-4% compatibilizer, 40%-55% PBAT, 5%-15% talc, and 1%-2% coupling agent. The PBAT degradation masterbatch of the present invention has excellent dispersion uniformity in PBAT, and the product has the characteristics of good color dispersion and excellent color stability; and also improves the material performance and degradation performance of the product to a certain extent.
[0004] CN104974478A provides a degradable plastic, the ingredients of which include: PBAT, corn starch, nano talc, modified calcium carbonate, compatibilizer, plasticizer, calcium stearate, antioxidant, and the weight ratio is: PBAT: 50-80 parts, corn starch: 10-30 parts, nano talc: 0-3 parts, modified calcium carbonate: 1-10 parts, compatibilizer: 1-7 parts, plasticizer: 3-15 parts, calcium stearate: 0.2-2 parts, antioxidant: 0.2-2 parts. The raw materials of the invention are low-cost and environmentally friendly, the manufacturing process is simple, the equipment requirements are not high, the manufacturing cost is low, and the product of the invention has a fast explanation speed and is green and environmentally friendly.
[0005] However, in the existing process, the amount of talc added is very low and cannot effectively improve the mechanical properties of plastic products. However, a high amount of talc (more than 30%) is easily separated from other substances (PBAT, starch, etc.) mixed together during the feeding process of producing degradable plastic particles, and the normal operation of production cannot be guaranteed. Since starch has a low degree of substitution, its modification effect on plastic products is also poor. Therefore, it is necessary to develop a method for preparing blown film particles using high-substitution esterified starch and high-content talc to meet application requirements. Summary of the invention
[0006] In view of the deficiencies in the prior art, the object of the present invention is to provide a method for preparing blown film particles, and a product and application thereof. The method provided by the present invention not only increases the amount of talcum powder used, thereby reducing production costs and improving the mechanical properties of the product, but also can realize continuous production of high-degree-of-substitution starch in the method, thereby better improving the degradability of the product.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing film-blown particles, the preparation method comprising the following steps:
[0009] (1) Starch and plasticizer are mixed, and then an esterifying agent is added for esterification; talcum powder is added for pre-dispersion; and PBAT is added for further dispersion to obtain a mixed material;
[0010] (2) Extruding the mixed material, cooling it, and pelletizing it to obtain the film blowing particles.
[0011] The method of the present invention has a simple preparation process, and the prepared blown film particles not only have good mechanical properties, but also have good degradability. In the method, starch is first esterified, and the esterified starch can effectively improve the starch gel texture, film-forming property, thermal stability, emulsification stability and other properties, improve the weakness of starch hydrophilicity, and thus improve the water-resistant and hydrophobic properties of subsequent plastic products; by adding talcum powder and PBAT in steps, the material can flow evenly and stably during the mixing process, which can effectively solve the problem of easy stratification when high-content talcum powder is mixed with other materials, so that each material is dispersed more evenly, so that the final obtained material has better performance in terms of tensile strength, elongation at break, etc.
[0012] Preferably, the added amounts of the raw materials prepared are 3-8 parts of plasticizer, 1-6 parts of esterifying agent, 10-30 parts of starch, 30-45 parts of talc, and 40-50 parts of PBAT in parts by weight.
[0013] In the present invention, the amount of the plasticizer added can be 3 parts, 4 parts, 5 parts, 6 parts, 7 parts or 8 parts, etc.;
[0014] The amount of the esterification agent added can be 1 part, 2 parts, 3 parts, 4 parts, 5 parts or 6 parts, etc.;
[0015] The amount of starch added can be 10 parts, 15 parts, 20 parts, 25 parts or 30 parts, etc.;
[0016] The amount of talc added can be 32 parts, 35 parts, 38 parts, 40 parts, 42 parts, 44 parts, etc.;
[0017] The added amount of the PBAT can be 42 parts, 44 parts, 45 parts, 47 parts or 49 parts, etc.
[0018] Any specific point value within the above numerical range can be selected, and will not be described in detail here.
[0019] Preferably, the plasticizer includes any one of propylene glycol, glycerol, sorbitol, and urea, or a combination of at least two of them.
[0020] Preferably, the esterification agent comprises vinyl acetate and / or acetic anhydride.
[0021] Preferably, the esterification agent is vinyl acetate and acetic anhydride.
[0022] Since starch is a polyhydroxyl natural polymer, there is a strong hydrogen bond between starch molecules. As a biomass material, starch has the disadvantages of poor water resistance and lack of melt processability. The esterified starch can not only overcome the above defects, but also significantly improve the mechanical properties and anti-hygroscopicity of the material after plasticization. In the present invention, vinyl acetate and acetic anhydride are particularly selected as esterifying agents, which can not only obtain starch with a higher degree of ester substitution, but also can be esterified without using an organic solvent, and the production process is safer and more environmentally friendly.
[0023] Preferably, the mass ratio of vinyl acetate to acetic anhydride is 1:(2-5), for example, it can be 1:2.5, 1:3, 1:3.5, 1:4 or 1:4.5.
[0024] Preferably, the mixing temperature in step (1) is 90-110° C. (for example, 92° C., 95° C., 98° C., 100° C., 102° C., 105° C. or 108° C.), and the mixing time is 20-50 min (for example, 25 min., 30 min., 35 min., 40 min. or 45 min.).
[0025] Preferably, the temperature of the esterification treatment in step (1) is 130-160°C (for example, 135°C, 140°C, 145°C, 150°C or 155°C, etc.), and the time is 30-60min (for example, 35min, 40min, 45min, 50min or 55min, etc.).
[0026] Preferably, the esterification treatment is carried out under vacuum negative pressure;
[0027] Preferably, the vacuum negative pressure value is -0.9 to -0.5 bar, for example, it can be -0.9 bar, -0.8 bar, -0.7 bar, -0.6 bar or -0.5 bar.
[0028] Preferably, the ester substitution degree of the esterified starch after the esterification treatment is 0.8-0.9.
[0029] Preferably, the rotation speed during the pre-dispersion in step (1) is 500-800 rpm, for example, it can be 550 rpm, 600 rpm, 650 rpm, 700 rpm or 750 rpm.
[0030] Preferably, the rotation speed during the pre-dispersion in step (1) is 600-700 rpm.
[0031] Preferably, the pre-dispersion time in step (1) is 12-15 min, for example, 12 min, 13 min, 14 min or 15 min.
[0032] As a preferred technical solution of the present invention, only when the rotation speed and dispersion time are within a specific range during pre-dispersion, the flow uniformity and stability of the mixed material are the best. Under this condition, adding PBAT to the mixture can obtain a uniform and stable blend, thereby making the various properties of the film-blowing particles better.
[0033] Preferably, the rotation speed during the dispersion in step (1) is 600-700 rpm, for example, it can be 610 rpm, 620 rpm, 630 rpm, 640 rpm, 650 rpm, 660 rpm, 670 rpm, 680 rpm or 690 rpm, etc.
[0034] Preferably, the dispersion temperature in step (1) is 90-110°C (for example, 92°C, 95°C, 98°C, 100°C, 102°C, 105°C or 108°C, etc.), and the dispersion time is 2-5min (for example, 2min, 3min, 4min or 5min, etc.).
[0035] Preferably, the extrusion in step (2) is carried out in a twin-screw extruder.
[0036] Preferably, the extrusion temperature in step (2) is 140-160°C, for example, 142°C, 145°C, 148°C, 150°C, 152°C, 155°C or 158°C.
[0037] Preferably, the rotation speed of the twin-screw extruder is 300-500 rpm, for example, it may be 320 rpm, 340 rpm, 360 rpm, 380 rpm, 400 rpm, 420 rpm, 440 rpm, 460 rpm or 480 rpm.
[0038] Any specific point value within the above numerical range can be selected, and will not be described in detail here.
[0039] In a second aspect, the present invention provides a film blowing particle, wherein the film blowing particle is prepared by the method described in the first aspect.
[0040] In a third aspect, the present invention provides a use of the blown film particles as described in the second aspect in the preparation of PBAT plastic products.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] The method of the present invention has a simple preparation process, and the prepared blown film particles have good mechanical properties. In the method, the starch is first subjected to esterification treatment, and the esterified starch can effectively improve the starch gel texture, film-forming property, thermal stability, emulsification stability and other properties, improve the weakness of the good hydrophilicity of the starch, and thus improve the water resistance and hydrophobicity of the subsequent plastic products; by adding talcum powder and PBAT in steps, the material can flow evenly and stably during the mixing process, and the problem of easy stratification when high-content talcum powder is mixed with other materials can be effectively solved, so that the materials are dispersed more evenly, so that the finally obtained material has better performance in terms of tensile strength, elongation at break and the like. DETAILED DESCRIPTION
[0043] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0044] Example 1
[0045] This embodiment provides a method for preparing film-blown particles, the method comprising:
[0046] (1) adding 20 parts of starch and 5 parts of urea to a high-speed mixer and mixing them at 100° C. for 35 minutes, then adding 1 part of vinyl acetate and 3 parts of acetic anhydride for esterification treatment, wherein the temperature of the esterification treatment is 140° C. and the time is 50 minutes. During the esterification treatment, the water obtained by the reaction is extracted by vacuuming at the end of the mixer, and the vacuum degree is -0.7 bar. The ester substitution degree of the starch after the esterification treatment is 0.9;
[0047] (2) adding 38 parts of talc powder for pre-dispersion for 13 minutes, wherein the speed of the mixer during the pre-dispersion is 650 rpm;
[0048] (3) Finally, 45 parts of PBAT were added and dispersed and stirred at 100° C. for 4 minutes. The speed of the mixer during the dispersion and stirring was 650 rpm to obtain a mixed material;
[0049] (4) The mixed material is added into a twin-screw extruder for extrusion at a temperature of 150° C. and a speed of 400 rpm, followed by cooling and pelletizing to obtain the film blowing particles.
[0050] Example 2
[0051] This embodiment provides a method for preparing film-blown particles, the method comprising:
[0052] (1) adding 25 parts of starch and 4 parts of propylene glycol to a high-speed mixer and mixing them at 110° C. for 30 minutes, and then adding 1 part of vinyl acetate and 2 parts of acetic anhydride for esterification treatment, wherein the temperature of the esterification treatment is 130° C. and the time is 40 minutes. During the esterification treatment, the water obtained by the reaction is extracted by vacuuming at the end of the mixer, and the vacuum degree is -0.8 bar. The ester substitution degree of the starch after the esterification treatment is 0.8;
[0053] (2) adding 42 parts of talc powder for pre-dispersion for 15 minutes, wherein the speed of the mixer during the pre-dispersion is 600 rpm;
[0054] (3) Finally, 40 parts of PBAT were added and dispersed and stirred at 110° C. for 3 minutes. The speed of the mixer during the dispersion and stirring was 700 rpm to obtain a mixed material;
[0055] (4) The mixed material is added into a twin-screw extruder for extrusion at a temperature of 140° C. and a speed of 450 rpm, followed by cooling and pelletizing to obtain the film-blowing particles.
[0056] Example 3
[0057] This embodiment provides a method for preparing film-blown particles, the method comprising:
[0058] (1) adding 15 parts of starch and 7 parts of glycerol to a high-speed mixer and mixing at 95° C. for 45 minutes, and then adding 1 part of vinyl acetate and 5 parts of acetic anhydride for esterification treatment, wherein the temperature of the esterification treatment is 150° C. and the time is 60 minutes. During the esterification treatment, the water obtained by the reaction is extracted by vacuuming at the end of the mixer, and the vacuum degree is -0.6 bar. The ester substitution degree of the starch after the esterification treatment is 0.9;
[0059] (2) adding 35 parts of talc powder for pre-dispersion for 12 minutes, wherein the speed of the mixer during the pre-dispersion is 700 rpm;
[0060] (3) Finally, 50 parts of PBAT were added and dispersed and stirred at 95° C. for 5 minutes. The speed of the mixer during dispersion and stirring was 600 rpm to obtain a mixed material;
[0061] (4) The mixed material is added into a twin-screw extruder for extrusion at a temperature of 160° C. and a speed of 350 rpm, followed by cooling and pelletizing to obtain the film blowing particles.
[0062] Example 4
[0063] This embodiment provides a method for preparing film-blown particles, the method comprising:
[0064] (1) adding 20 parts of starch and 5 parts of urea to a high-speed mixer and mixing them at 100° C. for 35 minutes, and then adding 4 parts of vinyl acetate for esterification treatment. The temperature of the esterification treatment is 140° C. and the time is 50 minutes. During the esterification treatment, the water obtained by the reaction is extracted by vacuuming at the end of the mixer. The vacuum degree is -0.7 bar. The ester substitution degree of the starch after the esterification treatment is 0.5;
[0065] (2) adding 38 parts of talc powder for pre-dispersion for 13 minutes, wherein the speed of the mixer during the pre-dispersion is 650 rpm;
[0066] (3) Finally, 45 parts of PBAT were added and dispersed and stirred at 100° C. for 4 minutes. The speed of the mixer during the dispersion and stirring was 650 rpm to obtain a mixed material;
[0067] (4) The mixed material is added into a twin-screw extruder for extrusion at a temperature of 150° C. and a speed of 400 rpm, followed by cooling and pelletizing to obtain the film blowing particles.
[0068] Example 5
[0069] This embodiment provides a method for preparing film-blown particles, the method comprising:
[0070] (1) adding 20 parts of starch and 5 parts of urea to a high-speed mixer and mixing them at 100° C. for 35 minutes, and then adding 4 parts of acetic anhydride for esterification treatment. The temperature of the esterification treatment is 140° C. and the time is 50 minutes. During the esterification treatment, the water obtained by the reaction is extracted by vacuuming at the end of the mixer. The vacuum degree is -0.7 bar. The ester substitution degree of the starch after the esterification treatment is 0.3;
[0071] (2) adding 38 parts of talc powder for pre-dispersion for 13 minutes, wherein the speed of the mixer during the pre-dispersion is 650 rpm;
[0072] (3) Finally, 45 parts of PBAT were added and dispersed and stirred at 100° C. for 4 minutes. The speed of the mixer during the dispersion and stirring was 650 rpm to obtain a mixed material;
[0073] (4) The mixed material is added into a twin-screw extruder for extrusion at a temperature of 150° C. and a speed of 400 rpm, followed by cooling and pelletizing to obtain the film-blowing particles.
[0074] Example 6
[0075] This embodiment provides a method for preparing film-blowing particles. The method is different from that of Embodiment 1 only in that the speed of the mixer during pre-dispersion in step (2) is 900 rpm and the pre-dispersion time is 10 min. The remaining steps are consistent with those of Embodiment 1.
[0076] Example 7
[0077] This embodiment provides a method for preparing film-blown particles. The method is different from that of Embodiment 1 only in that the speed of the mixer during pre-dispersion in step (2) is 400 rpm and the pre-dispersion time is 20 min. The remaining steps are the same as those of Embodiment 1.
[0078] Comparative Example 1
[0079] This comparative example provides a method for preparing film-blown particles, the method comprising:
[0080] (1) adding 20 parts of starch and 5 parts of urea to a high-speed mixer and mixing them at 100° C. for 35 minutes, then adding 1 part of vinyl acetate and 3 parts of acetic anhydride for esterification treatment, wherein the temperature of the esterification treatment is 140° C. and the time is 50 minutes. During the esterification treatment, the water obtained by the reaction is extracted by vacuuming at the end of the mixer, and the vacuum degree is -0.7 bar. The ester substitution degree of the starch after the esterification treatment is 0.9;
[0081] (2) adding 38 parts of talc and 45 parts of PBAT and dispersing and stirring at 100° C. for 17 minutes, wherein the speed of the mixer during the dispersing is 650 rpm, to obtain a mixed material;
[0082] (3) The mixed material is added into a twin-screw extruder for extrusion at a temperature of 150° C. and a speed of 400 rpm, followed by cooling and pelletizing to obtain the film blowing particles.
[0083] Comparative Example 2
[0084] This comparative example provides a method for preparing film-blown particles, the method comprising:
[0085] (1) adding 20 parts of starch and 5 parts of urea to a high-speed mixer and mixing them at 100° C. for 35 minutes, then adding 1 part of vinyl acetate and 3 parts of acetic anhydride for esterification treatment, wherein the temperature of the esterification treatment is 140° C. and the time is 50 minutes. During the esterification treatment, the water obtained by the reaction is extracted by vacuuming at the end of the mixer, and the vacuum degree is -0.7 bar;
[0086] (2) adding 45 parts of PBAT and dispersing and stirring at 100° C. for 4 minutes, with the speed of the mixer being 650 rpm;
[0087] (3) finally adding 38 parts of talc powder for pre-dispersion for 13 minutes, wherein the speed of the mixer during the pre-dispersion is 650 rpm, and finally obtaining a mixed material;
[0088] (4) The mixed material is added into a twin-screw extruder for extrusion at a temperature of 150° C. and a speed of 400 rpm, followed by cooling and pelletizing to obtain the film blowing particles.
[0089] Comparative Example 3
[0090] This embodiment provides a method for preparing film-blown particles, the method comprising:
[0091] (1) Add 20 parts of starch and 5 parts of urea into a high-speed mixer and mix at 100° C. for 35 minutes;
[0092] (2) adding 38 parts of talc powder for pre-dispersion for 13 minutes, wherein the speed of the mixer during the pre-dispersion is 650 rpm;
[0093] (3) Finally, 45 parts of PBAT were added and dispersed and stirred at 100° C. for 4 minutes. The speed of the mixer during the dispersion and stirring was 650 rpm to obtain a mixed material;
[0094] (4) The mixed material is added into a twin-screw extruder for extrusion at a temperature of 150° C. and a speed of 400 rpm, followed by cooling and pelletizing to obtain the film blowing particles.
[0095] Test example:
[0096] The film blowing particles prepared in Examples 1-7 and Comparative Examples 1-3 were put into a film blowing machine to prepare thermoplastic films, and various performance tests were performed on the films.
[0097] (1) Mechanical properties
[0098] The tensile strength was tested according to GB / T 1040.3-2006, the elongation at break was tested according to GB / T 1040.1-2006, and the tear strength was tested according to GBT 529-2008.
[0099] (2) Waterproof performance
[0100] The contact angle with water was tested using a fully automatic contact angle meter (equipment model DSA100). During the test, the water droplet size was 8 μL, and 5 points were taken for each sample to calculate the average value (retain the integer).
[0101] The results are shown in Table 1.
[0102] Table 1
[0103]
[0104] It can be seen from the data in Table 1 that the contact angle of the film prepared by the film blowing particles of Examples 1-3 with water is above 130°, indicating that the film blowing particles prepared by the present invention have good hydrophobic properties; the tensile strength of the samples of Examples 1-3 is between 26.4-28.3 MPa, the elongation at break is between 673%-697%, and the tear strength is between 79.3-82.7 kN / m, indicating that the film blowing particles of the present invention have excellent mechanical properties.
[0105] It can be seen from Examples 1, 4 and 5 that only by using a combination of vinyl acetate and acetic anhydride as an esterifying agent to esterify starch can the ester substitution degree of starch be higher, and thus the waterproof performance of the resulting blown film particles can be better;
[0106] It can be seen from Examples 6 and 7 that when the speed and stirring time during pre-dispersion are within the range specified in the present invention, the flow uniformity and stability of the mixed material are better. Under this condition, adding PBAT to the mixture can obtain a blend with better flow uniformity and stability, thereby making the various properties of the film-blowing particles better;
[0107] It can be seen from Comparative Examples 1-2 that when the order of adding the raw materials is not the order specified in the present invention, stratification will occur during the preparation process due to the high content of talc, and the performance of the film-blown particles finally obtained is poor;
[0108] It can be seen from Comparative Example 3 that when the starch is not esterified, the resulting blown film particles have poor waterproof properties.
[0109] In summary, the method described in the present invention can only make the film-blowing particles of the present invention have extremely strong waterproof performance and greatly improve various mechanical strengths, such as tensile strength, tear strength, etc., under specific process parameters and raw material addition sequence.
[0110] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate a method for preparing a film-blown particle, its product and application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
[0111] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0112] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
Claims
1. A method for preparing blown film particles, characterized in that: The preparation method comprises the following steps: (1) Starch and plasticizer are mixed, and then an esterifying agent is added for esterification; talcum powder is added for pre-dispersion; and PBAT is added for further dispersion to obtain a mixed material; (2) extruding the mixed material, cooling it, and pelletizing it to obtain the film blowing particles; The addition amount of the raw materials prepared by weight is 3-8 parts of plasticizer, 1-6 parts of esterifying agent, 10-30 parts of starch, 30-45 parts of talc, and 40-50 parts of PBAT; The esterifying agent is vinyl acetate and acetic anhydride in a mass ratio of 1:(2-5).
2. The method for preparing blown film particles according to claim 1, characterized in that: The plasticizer includes any one of propylene glycol, glycerol, sorbitol, and urea, or a combination of at least two of them.
3. The method for preparing blown film particles according to claim 1, characterized in that: The mixing temperature in step (1) is 90-110° C. and the mixing time is 20-50 min.
4. The method for preparing blown film particles according to claim 1, characterized in that: The temperature of the esterification treatment in step (1) is 130-160° C. and the time is 30-60 min.
5. The method for preparing blown film particles according to claim 1, characterized in that: The esterification treatment is carried out under vacuum negative pressure.
6. The method for preparing film-blown particles according to claim 5, characterized in that: The vacuum negative pressure value is -0.9 to -0.5 bar.
7. The method for preparing blown film particles according to claim 1, characterized in that: The rotation speed during the pre-dispersion in step (1) is 500-800 rpm.
8. The method for preparing blown film particles according to claim 1, characterized in that: The rotation speed during the pre-dispersion in step (1) is 600-700 rpm.
9. The method for preparing blown film particles according to claim 1, characterized in that: The pre-dispersion time in step (1) is 12-15 minutes.
10. The method for preparing blown film particles according to claim 1, characterized in that: The rotation speed during the dispersion in step (1) is 600-700 rpm.
11. The method for preparing blown film particles according to claim 1, characterized in that: The dispersion temperature in step (1) is 90-110° C. and the dispersion time is 2-5 min.
12. The method for preparing blown film particles according to claim 1, characterized in that: The extrusion in step (2) is carried out in a twin-screw extruder.
13. The method for preparing blown film particles according to claim 1, characterized in that: The extrusion temperature in step (2) is 140-160°C.
14. The method for preparing blown film particles according to claim 12, characterized in that: The rotation speed of the twin-screw extruder is 300-500 rpm.
15. A film-blown particle, characterized in that: The film blowing particles are prepared by the method according to any one of claims 1 to 14.
16. Use of the blown film particles according to claim 15 in the preparation of PBAT plastic products.
Citation Information
Patent Citations
Biodegradable plastic and production process thereof
CN104974478A
PBAT degradation color master batch and preparation method thereof
CN108059804A
Organic and inorganic filled PBAT (poly(butylene adipate-co-terephthalate)) completely biodegradable material composition and particles and film prepared from same
CN113444346A
Low-temperature heat-sealing biodegradable composite film and preparation process thereof
CN114889285A
